(untitled) (Research, Society and Development, 2020)
The concern about climate change and its impacts has been the objective of negotiations worldwide. Both companies and government entities have made continuous efforts to reduce greenhouse gases, limit the increase in global temperature and promote resilience to climate change. Thus, we sought to analyze in this study the history of emissions in Brazil and the way in which the country has adapted to international requirements. Based on a systematic review of the PRISMA model (Preferred Reporting Items for Systematic Reviews and Meta-Analysis), 21 scientific articles were analyzed, and then a quantitative study of the greenhouse gas emissions inventories, published by the Brazilian GHG Protocol Program, per part of organizations in the Civil Construction sector, was developed. For the sector, nine member organizations were counted, four of which have the gold seal. The results showed that the publications of the inventories are concentrated in organizations located in the Southeast region of the country and that, in general, there is no periodicity in the publications. It was also noticed that 93.8% of the emissions registered in 2019 are included in Scope 3, that is, originated from indirect sources, such as in the production of cement and steel used in the works. Finally, it was observed that Civil Construction organizations make up a percentage of 6% of the companies that are members of the Program, highlighting the need of the sector to expand the management of their emissions, in order to contribute with measures to combat climate change.